Hadith #3826 - Sunan Abi Dawud - Abbas bin 'Abdul 'Azeem al-'Anbari عباس بن عبد العظيم العنبري; Abu 'Amir al-'Aqdi عبد الملك بن عمرو القيسي أبو عامر العقدي; Khalid bin Mysrh al-Tfawy خالد بن ميسرة الطفاوي; Mua'wiya bin Qurrah bin Iyas معاوية بن قرة بن إياس بن هلال; Qurrah bin Iyas (Sunan Abi Dawud)
I ate garlic and came to the place where the Prophet (ﷺ) was praying; one rak’ah of prayer had been performed when I joined. When I entered the mosque, the Prophet (ﷺ) noticed the odour of garlic. When the Messenger of Allah (ﷺ) finished his prayer, he said: He who eats from this plant should not come near us until its odour has gone away. When I finished the prayer, I came to the Messenger of Allah (ﷺ) and said: Messenger of Allah, do give me your hand. Then I put his hand in the slee
Grade: Sahih